Mitochondrial DNA of CO1 and 16S rRNA genes for diversity and phylogenetic analysis of sardine (Sardinella spp.) from the Lombok Straits, Indonesia - H. MAHRUS; AGIL AL IDRUS; ABDUL SYUKUR (Society for Indonesian Biodiversity, 2024)
Abstract. Mahrus H, Idrus AA, Syukur A. 2024. Mitochondrial DNA of CO1 and 16S rRNA genes for diversity and phylogenetic analysis of sardine (Sardinella spp.) from the Lombok Straits, Indonesia. Biodiversitas 25: 3500-3509. Sardines in Indonesia consist of six species from around 21 species- world, having many similarities and difficulty distinguishing between one species and others caused the taxonomy of the Sardines species is still ambiguous affected the same names in two different species and the different names in one species because of morphological similarities. The most effective method for identifying animal species and subspecies is the molecular method using sequences of the cytochrome c oxidase subunit 1 (CO1) gene and the 16S rRNA gene. The study aims to determine the molecular characteristics, genetic diversity, and phylogenetic relationships of sardines in the Lombok Strait using a sequence of CO1 and 16S rRNA genes. The study has significant practical implications as it can potentially inform conservation efforts and fisheries management. The sardine samples were collected from the Lombok Strait by small-scale fishermen. The sampling method was random. It takes 55 individuals as a sample. Initially, the sardine samples were grouped based on morphological characteristics. Subsequently, DNA from the two genes of 20 sardine samples were separated and amplified using two pairs of primers. The DNA amplification yielded 671 bp for the CO1 gene and 625 bp for the 16S rRNA gene. The sequence data from the two genes were analyzed using Molecular Evolutionary Genetics Analysis Version 11 (MEGA 11). The CO1 gene sequence revealed that sardines from the Lombok Strait could be determined more accurately than the 16S rRNA. CO1 rRNA genes of 12 individuals indicated a close genetic relationship between sardines of Lombok Strait and Sardinella aurita Valenciennes 1847, and the 16S rRNA gene placed sardines from Lombok Strait as an out-group. It empirically demonstrates that the CO1 gene is more effective than the 16S rRNA gene in identifying and determining molecular characteristics, genetic diversity, and phylogenetic relationships of sardines in Lombok Strait.